The Role of Wives in Providing Family Financial Support: An Islamic Legal Perspective - Azwandi, Azwandi; Jeri, Edwin; Ihsan, Sartika Fortuna (Samara: Journal of Islamic Law and Family Studies, 2025)
This article discusses the Islamic legal perspective on the role of wives in providing for their families. This study uses a qualitative descriptive method, which systematically, factually, and accurately describes the facts that occur in the field. The data collection methods used in this study are observation, interviews, and documentation. The role of wives in helping their families' finances includes independent sales efforts. All of these are efforts to help the family's finances, which aim to meet the family's needs and also to develop their potential, so that there is a change in conditions from deficiency to stability. The reasons wives work outside the home are their husbands' insufficient income and increasing living expenses. The role of wives in helping the economy. In the view of Islamic law, the role of wives in helping the family economy is permissible, but with the conditions that they must follow Islamic law and obtain permission from their husbands, and that it is the obligation of a husband to provide for his wife, even if she has her own income. The view of Islamic law regarding the role of wives who work to help the family economy is very important if it is applied in accordance with the provisions of Islamic law. By applying Islamic law, wives working outside the home become consistent with the principles of Islamic law. The Islamic legal perspective guarantees transparency, fairness, and compliance with Islamic law principles in the role of wives in supporting the family economy. The application of Islamic legal principles can provide greater benefits and give a clearer picture of the role of wives in supporting the family economy.